Sostav tela i fiziceskaja podgotovlennost' prygunov na lyžach s tramplina 16-20 let - Pikhaev, R. R.; Salavatov, K. A.; Musayev, A. S. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The study was conducted in 2019 on the basis of the Federal program for winter sports "snowflake" named after A.A. Danilov (Tchaikovsky), together with Plekhanov Russian University of Economics, which was attended by 47 athletes (20 girls and 27 boys), 16-21 years of age, qualification-masters of sports and candidates for master of sports. Athletes highly appreciated the individual sports card, recommendations for sports training, concerning individual vulnerable physical qualities and technical actions. The fat component in girls was 18.4%, and in 2019 it was 13.4%. In boys, the percentage of adipose tissue has minimal values: in 2018, 9.6%. In 2019 - 9.4%. The experiment revealed that the boys significantly improved the results in four control exercises, especially in static muscle strength ("plank") from 138 to 174 seconds. The girls improved indicators in only three control exercises.